2008
DOI: 10.1016/j.otohns.2008.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Second free tissue transfers in head and neck reconstruction

Abstract: A second free tissue transfer is a viable resource in head and neck reconstruction. Acceptable rates of flap survival and complications are encountered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…Novakovic et al as well as others have shown that the reason flaps fail within 48 hours is mostly due to vascular occlusion: venous problems (35%) and arterial problems (28%). As the time period extends beyond 48 hours the gap between arterial problems and venous problems widens, with 83% of flap failure secondary to venous compromise and 8% related to arterial compromise, and these numbers are similar in other studies as well . When detected early enough, intervention can salvage up to 65% to 84% of these failing flaps …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Novakovic et al as well as others have shown that the reason flaps fail within 48 hours is mostly due to vascular occlusion: venous problems (35%) and arterial problems (28%). As the time period extends beyond 48 hours the gap between arterial problems and venous problems widens, with 83% of flap failure secondary to venous compromise and 8% related to arterial compromise, and these numbers are similar in other studies as well . When detected early enough, intervention can salvage up to 65% to 84% of these failing flaps …”
Section: Discussionsupporting
confidence: 70%
“…As the time period extends beyond 48 hours the gap between arterial problems and venous problems widens, with 83% of flap failure secondary to venous compromise and 8% related to arterial compromise, and these numbers are similar in other studies as well. 4,11,[13][14][15][16][17] When detected early enough, intervention can salvage up to 65% to 84% of these failing flaps. 11,17 Disa et al, 1 in their 1999 study, demonstrated an overall flap loss rate of 2.3% over an 11-year span, of which 5 of the 77 buried flaps (6.5%) were lost.…”
Section: Discussionmentioning
confidence: 99%
“…For example, McCarn and colleagues reported their experience with second free tissue transfer in the head and neck; they found that free flap survival in revision free flaps matched that of primary free flap reconstructions (97% versus 95%, respectively) 5. In this cohort, the most common reasons for a second reconstructive procedure were tumor recurrence (53%), tissue defects (exposed bone, hardware, or vessels, fistula; 22%), and osteoradionecrosis (8%).…”
Section: Discussionmentioning
confidence: 94%
“…Owing to the rich vascularity of the head and neck, satisfactory recipient blood vessels seem to be available even in patients who have undergone prior resection and one or more prior free flap reconstructions. [14][15][16] We had good success re-using vessels that had previously been used for the initial free flap, with no flap losses occurring when this technique was used. 7,17 Obviously, the surgeon must ensure that the recipient vessel has adequate flow and was not the source of pedicle thrombosis, for example, because of intimal injury.…”
Section: Discussionmentioning
confidence: 95%